The competition activity of elite cross-country skiers during the 2006-2007 season - Eepulenas, E. (Abstractbook. The First International Low Lands Congress on Science and Skiing, Brussels, October 11th, 2008)
The goal of this research is examination of the contention activity of the world elite skiers during the season of 2006-2007 and determination of the scope, structural elements and peculiarities of their contention activity. The subject of this research is the contention activity of the ski racers, who won medals at the World Ski Championship of 2007 and the skiers, who were among the 30 best in the general record of the competitions of the Ski World Cup. The following methods were used for this research: study of the literature resources, analysis of the documents. Conclusions. The world elite skiers can be divided into the following groups: universal skiers stayer type; universal skiers sprinter type; long distance skiers; skiers-sprinters. The analyses of the influence of the skiing physical loads to the bodies of the skier allow presuming that preparation of the women skiers for various distance competitions will be done with regard to the individual genetic type and specific individual capabilities.